ABCG2 (BCRP) m RNA expression level by using real- time PCR and immunohistochemistry associated with clinicopathological features in Iraqi women with stage II-III breast cancer. - Mahmood, Noah A. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: Breast cancer is the most frequent cancer and cause of death among women worldwide. ABCG2 (ATP–binding cassette sub-family G member 2) is an ABC transporter superfamily and endogenous expression of ABCG2 in different certain cancer reflect intrinsic drug resistance. It is also a molecular determinant of pharmacokinetic properties of many drugs in humans. In this study, we determined the expression levels of ABCG2 in breast tissues of Iraqi women with stage II and III breast cancer. The correlation between the expression levels of ABCG2 and clinicopathological features was analyzed. Methods: The expression levels of ABCG2 in the breast was determined by using real- time PCR and immunohistochemistry in 64 patients with stage II and III samples and in 21 benign tumors from Iraqi women. Results: We found that the expression level of ABCG2 mRNA were significantly increased in breast cancer stage II-III tissues than those in benign tumor tissues. There was a significant variation between the mRNA levels of ABCG2 in stage II and stage III at P< 0.05. Immunohistochemistry revealed that the protein expression levels of ABCG2, was also increased in 83% of patients with stage II and III breast cancer as compared to 17% in benign tumor. The increased expression levels of ABCG2, in stage II-III breast cancer were correlated to tumor stages (P=0.03), tumor grades (P=0.01), tumor types (P=0.01) and lymph node metastasis (p=0.0001), respectively. Conclusion: ABCG2 expression level in Iraqi women with stage II and III breast cancer were highly correlated with tumor stages, grades, types and metastasis and they could be used a potential markers which can prediction tumor behavior, progression and prognosis. Over expression of ABCG2 protein lead to treatment failure, tumor relapse and tumor metastasis by induction cancer cells against cytotoxic drugs.